Estudo da diversidade genética em peixes de igarapés da bacia do rio Tapajós: uma abordagem de sistemática molecular utilizando-se DNA Barcoding - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2013)
The Amazon basin has the greatest diversity of fishes of Brazil in its various environments, such as lowland forest streams, common in the Amazon. Streams are found in fish species with high endemism and little studied in relation to fish of high commercial value. For characterization of fish populations in such environments the use of active sampling with the use of hand nets and seine nets has achieved satisfactory results. The DNA barcoding molecular tool is used to characterize species in various types of animals, including fish, through the use of a mitochondrial marker region I. Cytochrome oxidase The present study aimed to characterize the fish fauna of four streams upland 1st or 2nd orders in the Santarém region through the use of active collecting in stretches 50 feet each stream and traditional and molecular identification of the collected specimens. A total of 836 fish collected reached a total of 20 different species, belonging to 20 genera, 14 families and 6 orders in these three streams, with the predominance of Characiformes, Siluriformes and Gymnotiformes, respectively. Further, by using the technique of DNA barcoding, 69 12 different sequences were obtained from species analyzed environments, occurring 75% of consensus between the traditional identification and molecular intraspecific divergence occurring above the threshold of 3.5%, which was adopted as delimiter in species barcoding in Bryconops giacopinii, Hypessobrycon heterorhabdus and Aequidens tetramerus, suggesting new analyzes in these groups to be no consensus on whether there is only one specie.
Keywords: Bacia Amazônica; Igarapés; Peixes; DNA barcoding; CNPQ::CIÊNCIAS EXATAS E DA TERRA; ESTUDOS E MANEJOS DE ECOSSISTEMAS AMAZÔNICOS